Physical Exercise Reduce Fatigue in Children With Leukemia - Apriyanti Apriyanti; Mayetti Mayetti; Deswita Deswita (Poltekkes Kemenkes Jakarta III, 2021)
Fatigue is a complaint that many children with Acute lymphoblastic leukemia (ALL) feel while undergoing chemotherapy and is a multidimensional problem. The condition of fatigue that children continuously feel requires treatment from health workers. To optimize physical exercise interventions, researchers combined physical exercise with Levine theory based on four conservation principles to increase patient activity during treatment. The goal of the study was to provide physical exercise to children with ALL undergoing chemotherapy. The research method is quantitative with Quasy Experimen With Control Group Pre-Test-Post-Test Design. This study sample of ALL children aged 8-13 years who underwent maintenance phase chemotherapy. The sample was taken using consecutive sampling techniques with a total of 22 people. The data collection tool uses the Multidimensional Fatigue Scale questionnaire. The results showed that the average fatigue scale in the pre-test intervention group was 31.18 and post-test 47.64. The pre-test control group was 27.27 and post-test 39.18. The level of fatigue experienced by children decreased (p 0.000) after being given physical exercise walking 5 minutes, six times in 14 days. The involvement of health workers is expected in conducting a comprehensive assessment of fatigue symptoms, and the results of this study can be used as one of the physical exercise interventions in the management of fatigue in children with leukemia.